Healthy Lifestyle Behaviours are Associated with Lower Probability of Having Cardiovascular Disease Risk Factors - M Akbartabartoori; CR Hankey; MEJ Lean (Tehran University of Medical Sciences, 2005)
Healthy lifestyle behaviors are associated with lower risk of having cardiovascular disease (CVD). There is a cluster of risk factors that predisposes people to CVD. Overweight/obesity, unhealthy diet, inactivity, and smoking are major lifestyle risk factors for CVD, which are also associated with other potent clinical risk factors including raised plasma lipids, coagulation factors and measures of inflammation. This study aimed to evaluate the association between lifestyle factors and some established clinical cardiovascular risk factors: C-reactive protein (CRP), total cholesterol, HDL-C, non-HDL-C and fibrinogen in Scottish adults with a high prevalence of CVD. Cross-sectional data from 5460 participants aged 16-74 years whom had valid biochemical measurements in the Scottish Health Survey (SHS) 1998 were analysed. Trained staff obtained anthropometric measures. Levels of physical activity, cigarette smoking, alcohol intake and dietary habits were measured by questionnaires. Non-HDL-C was calculated by subtracting HDL-C from total cholesterol. Data analysis was carried out using SPSS with different statistical tests. After adjusting for age, body mass index (BMI) was significantly associated with all risk factors in both sexes as obese subjects had the highest concentrations of CRP, total and non-HDL-C and fibrinogen, and the lowest concentrations of HDL-C (P< 0.01) compared to BMI< 25 kg/m². Cigarette smoking was positively associated with CRP, fibrinogen (P< 0.0001) and negatively with HDL-c in all subjects, and positively with total cholesterol and non-HDL-C in women (P< 0.01). Men and women who were inactive had the highest concentrations of CRP and fibrinogen and lowest concentration of HDL-C compared with active subjects (P< 0.001). Those subjects who consumed ≥ 400 grams fruits and vegetables per day had lowest CRP and fibrinogen (P< 0.001). Total fruit and vegetable consumption had a positive association with HDL-C concentration and negative association with non-HDL-C concentration only in women (P< 0.01). Men who consumed 1-21 units of alcohol per week and women who consumed 7-14 had lower CRP concentrations (P< 0.01). Alcohol consumption showed a positive association with HDL-C (P< 0.0001). Multivariate analysis produced slightly different results when analyzed with GLM, logistic and linear regression methods. However, all three methods confirmed that when all independent variables have been entered simultaneously in the models, BMI and smoking were the most important variables for the risk factors (P< 0.01). The odds ratios of having CRP ≥ 3mg/l, fibrinogen ≥ 3g/l, non-HDL-C > 4 mmol/l and HDL-c ≤ 1 mmol/l for obese subjects compared with BMI